Menangkal Genosida Agama dengan Pendidikan Islam Berbasis Multikultural - Amru Almutasim (FALASIFA : Jurnal Studi Keislaman, 2016)
Diversity has become a part of history and the reality of human life, so he was a natural phenomenon whose existence can not be denied. But in concrete reality, diversity has made man trapped in a destructive attitudes. The existence of conflicts between different communities with a background of SARA (Tribe, Religion, Race and intergroup). Of the many triggers, the factors of religious differences, even differences in religious ideology, is a factor that can not be excluded. Cases of violence and war in various parts of the world, shows how religion has been used as a means of "destruction" of humans, where it is so contrary to the teachings of all religions It shows that for centuries, the history of interactions among religious is much influenced by suspicion and hostility on the pretext can achieve the pleasure of God and for the sake of spreading the good news that comes from the Almighty, in terms of truth, every religion teaches peace, togetherness at once to spread the mission of the benefit Â Keywords:Â Multicultural values,Â Islamic education, Religion